Malaysia’s Security Laws: Arrest and Detention under Security Offences (Special Measurements) Act 2012 - Sulaiman, Nur Fazini Asro bt Ramzi; Jalil, Datin Faridah (International Journal of Psychosocial Rehabilitation, 2020)
SOSMA 2012 or the Security Offences (Special Measurements) Act 2012 was commenced on 22nd June 2012. Since its birth, SOSMA (“the Act”) has invites debates and heated arguments from every level in the legal fraternity on its content. The most controversial issues are on arrest and detention of the detainee charged under the Act which is said to be unconstitutional and thus, violates the basic fundamental human rights. This paper will discuss specifically issues on arrest and detention stated in the Act. The objective of this paper is to see on how the laws is carried out and whether there is a lacuna on the procedural law. The study of this paper will be focusing on decided cases and comparisons to other security laws in Malaysia. The study is important as to see how the laws is being carried out without violation of any fundamental human rights. Through this study, it is hoped that it will assist a better understanding on how the laws is carried and executed, for further references in the future. Shall there is a lacuna procedurally, this study will assist to suggests and propose for better execution on the subject matter involved.